DYNAMIC SEARCH FOR ERRORS IN INDUSTRIAL INTERNET PROTOCOLS FOR APPLICATION IN MULTISENSOR CONTROL SYSTEMS - Klym , Halyna; Dіachok , Roman (Computer systems and information technologies, 2022)
Based on the considered theory of dynamic damage analysis of industrial Internet protocols and determination of the necessary data of dynamic multimodal communication of the sensor, the method of fuzzy tests in combination with dynamic multimodal data transmission for jamming in multisensor control systems is proposed. The proposed method traces program execution, finds input fields affecting conditional branches through dynamic damage analysis, and captures the dependency of conditional branches to appropriately control test case grammar generation, increasing deep-level code execution. The results of the comparative experiment confirm that the method to some extent improves the validity of test cases and the speed of code coverage, as well as increases the probability of detecting anomalies in the implementation of the protocol. To evaluate multi-sensor computerized systems from the point of view of "fuzzy intelligence", studies were conducted to solve the problem of low code coverage caused by repeated execution of test sequences on the same path, starting from the system program level in the implementation of industrial Internet protocols and the prerequisite of obtaining affordable weekends program codes, or an executable binary file. The paper proposes a method that is combined with dynamic multimodal transmission of sensor data in a fuzzy processing program. It provides program execution, protocol implementation, finds input fields that affect conditional branches using dynamic inconsistency analysis, and captures dependency relationships between conditional branches to control test generation.